Brain-derived Neurotrophic Factor Is Associated with Cognitive Impairment in Elderly Korean Individuals - Lee, Sang Jun (Clin Psychopharmacol Neurosci, 2015)
OBJECTIVE: Brain-derived neurotrophic factor (BDNF) is a neurotrophin that is widely expressed in the mammalian brain and acts to regulate neuronal survival and influence cognitive processes. The present study measured serum BDNF levels to investigate the associations of the BDNF Val66Met and 5-hydroxytryptamine transporter linked promoter region (5-HTTLPR) polymorphisms with cognitive function in elderly Korean individuals. METHODS: Over 60 years, a total of 834 subjects were recruited for the present study. The subjects were classified into groups based on the degree of cognitive impairment (age-associated cognitive decline, mild cognitive impairment, and Alzheimer’s disease) and compared with normal controls in terms of a neuropsychological assessment and a clinical evaluation. RESULTS: Of the initial 834 study participants, 165 (59 controls and 106 subjects with cognitive impairments) completed the study. There was a significant increase in serum BDNF levels in subjects with cognitive impairments relative to the control group and the BDNF Val66Met polymorphism was significantly associated with cognitive function but not serum BDNF levels. The 5-HTTLPR polymorphism did not have any associations with cognitive impairment or serum BDNF levels. CONCLUSION: The present findings suggest that BDNF may play a role in the pathophysiology of cognitive impairment and the BDNF Val66Met polymorphism may be an important factor in the susceptibility to these age-related deficits.